2017
DOI: 10.19080/nfsij.2017.03.555615
|View full text |Cite
|
Sign up to set email alerts
|

Native and Modified Starches as Matrix for Edible Films and Covers

Abstract: Among the natural n-polymers for to elaborate edible films is the starch. Though, it by itself can not to develop satisfactorily the properties to produce an adequate film. Native starches have several drawbacks associated to their hydrophilic properties that limit its function as barrier. The plasticizers, improves the characteristics and properties of the films, in addition it has been used native starch reinforced with non-starchy components, as palliative. However, a best solution could be the use of modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Our results were in similarity to theirs that all coated fillets had lower PV than the control and shows that Gel/Ch coating could efficiently decrease lipid oxidation in fillets (Nowzari et al, 2013). It is demonstrated that chitosan, starch, and gelatin may be considered as the natural barriers against oxygen permeation and chitosan is presumed as a potential natural antioxidant for stabilizing lipid‐containing foods (Jonaidi Jafari et al, 2018; Perez Sira & Dufour, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Our results were in similarity to theirs that all coated fillets had lower PV than the control and shows that Gel/Ch coating could efficiently decrease lipid oxidation in fillets (Nowzari et al, 2013). It is demonstrated that chitosan, starch, and gelatin may be considered as the natural barriers against oxygen permeation and chitosan is presumed as a potential natural antioxidant for stabilizing lipid‐containing foods (Jonaidi Jafari et al, 2018; Perez Sira & Dufour, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonds are responsible for the low mobility of starch molecules and, consequently, for the typical lower flexibility of these bioplastics when compared to conventional synthetic plastics [8]. This limitation can be fixed through the addition of plasticizers and organic substances incorporated in different concentrations into the starch gel to improve the film's mechanical properties.…”
Section: Starch-based Bioplastics Physicochemical Propertiesmentioning
confidence: 99%
“…Concurrently, there is a concerted effort to develop alternative products from renewable and natural resources that can degrade more quickly after disposal. In this context, eco-efficient packaging stands out, produced using materials that respect the ecological, economic, and social premises of sustainability, with a focus on polymers derived from biomass [8,9]. Apart from being sourced from inexhaustible supplies, these materials appear to be capable of ensuring the quality of both fresh and processed food products [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of a plasticizer for edible film/coating formulation should consider the adaptability and persistence of the plasticizer, as well as the required physical characteristics for the developed film/coating. Glycerol has been the plasticizer most frequently used to formulate films/coatings to be applied on fruit and vegetables [ 2 , 20 , 23 , 28 ], providing increased moisture content and gas permeability to these structures when compared to other plasticizers (e.g., sorbitol) [ 35 ].…”
Section: Materials Used To Formulate Probiotic-loaded Edible Films/coatings For Application To Fresh and Minimally Processed Fruit And Vementioning
confidence: 99%